The use of coins as a figural iconographic resource: Concercning on some lychnological finds in Augusta Emerita - González Blas, Alejandro; Bustamante-Álvarez, Macarena; Moreno Pulido, Elena (Conimbriga, 2024)
We present two ceramic fragments of decorated lamps from the old site of Augusta Emerita. Their interest lies in presenting a decoration based on the printing of two Roman Imperial coins and in appearing contextualized so that we can provide chronological data of final use. This work allows us to approach, without claiming to be an exegesis, the phenomenon of coin impressions on various supports and delve into other craft practices.